Impact of conventional cigarette and electronic cigarette use on sperm quality and IVF/ICSI outcomes - Hye Kyeong Kim; Won Yun Choi; Jin Il Lee; Tae Jin Kim (Scientific Reports)
Abstract Purpose Electronic cigarettes (E-cigarettes) vaporize a liquid containing glycol, nicotine, and various additives, providing an alternative to traditional smoking. Although they contain only 5% of the harmful substances found in traditional cigarettes, E-cigarettes still pose potential health risks. This study conducted a retrospective analysis of the impact of conventional cigarette and E-cigarette smoking on male in vitro fertilization (IVF) outcomes. Method Between May 2022 and January 2024, the study included 151 conventional cigarette smokers and 145 E-cigarette smokers who were undergoing IVF. The study focused on infertility primarily caused by tubal factors, polycystic ovarian syndrome, abnormal thyroid function, and hyperprolactinemia. The primary outcomes measured included the number of retrieved oocytes, the number of 2-pronuclear (2PN) embryos, fertilization rate, implantation rate, ongoing pregnancy rate, and live birth rate. Secondary outcomes included semen parameters. Results Results showed a higher live birth rate in the E-cigarette group compared to the conventional cigarette group (p = 0.011). The E-cigarette group also had significantly lower basal serum prolactin levels (p = 0.029) and higher sperm motility (p = 0.014). Significant predictors of live birth included male body mass index, male FSH levels, parity, and the number of 2PN embryos. Multivariate analysis identified male serum FSH levels, and the number of 2PN embryos as independent factors associated with successful live births. Conclusion E-cigarettes may be less harmful than conventional cigarettes in terms of semen motility and live birth rates in IVF couples.